2022
DOI: 10.2147/dddt.s368836
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin and Its Analogs: Potential Protective Agents Against Atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disease of the artery wall associated with lipid metabolism imbalance and maladaptive immune response, which mediates most cardiovascular events. First-line drugs such as statins and antiplatelet drug aspirin have shown good effects against atherosclerosis but may lead to certain side effects. Thus, the development of new, safer, and less toxic agents for atherosclerosis is urgently needed. Diosgenin and its analogs have gained importance for their efficacy against lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 178 publications
0
9
0
Order By: Relevance
“…The most stable SM on IL2 was diosgenin, suggesting that the diosgenin is a representative compound in saponin derivatives [ 56 ]. A report shows that diosgenin reduces triglyceride content in the liver, and stimulates the excretion of cholesterol [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most stable SM on IL2 was diosgenin, suggesting that the diosgenin is a representative compound in saponin derivatives [ 56 ]. A report shows that diosgenin reduces triglyceride content in the liver, and stimulates the excretion of cholesterol [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…dioscin (diS) is an active ingredient of dioscoreaceae herbs with a number of biological activities (11). Its pharmacological effects are extensive, mainly involving the heart, liver, lung, kidney and other organs, with anti-inflammatory, anti-fibrotic, anti-tumor, anti-atherosclerotic, immunomodulatory and modulating oxidative stress responses (11)(12)(13)(14)(15). The regulation of the nF-κB pathway can trigger inflammatory responses (16).…”
Section: Mechanism Of Dioscin Ameliorating Renal Fibrosis Through Nf-...mentioning
confidence: 99%
“…The regulation of the NF-κB pathway can trigger inflammatory responses ( 16 ). Studies have found that DIS can diminish the expression of inflammatory factors by inhibiting the phosphorylation of NF-κB p65 and thus suppress the inflammatory response ( 13 , 14 ). In addition, it has been found that DIS could reduce renal fibrosis by upregulating the Sirt3 signal ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dioscin is composed of diosgenin and a sugar chain on the C-3 hydroxyl group [ 17 ]. Recent data suggested that dioscin and its hydrolysis product diosgenin play an anti-atherosclerotic role through their anti-inflammatory, antioxidant, plasma cholesterol-reducing, anti-proliferation and anti-thrombotic effects [ 105 ].…”
Section: Dioscinsmentioning
confidence: 99%